THE EFFECT OF BRAND AWARENESS, BRAND IMAGE, AND PRODUCT QUALITY ON PURCHASE DECISIONS FOR FRESTEA PRODUCTS IN BATAM CITY - Fery Afrizal; Nora Pitri Nainggolan (International Journal Management and Economic, 2026)
This study aims to analyze the effect of brand awareness, brand image, and product quality on purchasing decisions of Frestea products in Batam City. This research uses a quantitative approach with a survey method. The data were collected by distributing questionnaires to 119 respondents who are consumers of Frestea in Batam City. The data analysis techniques used in this study include descriptive statistical analysis and multiple linear regression analysis using SPSS software. The results of the study show that brand awareness, brand image, and product quality have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings indicate that strengthening brand strategies and improving product quality are important factors in increasing consumer purchasing decisions.